Effect of noise and green space exposure on depression, anxiety and stress among the Lebanese population - Raseel Youssef; Nour Dassuki; Dania El Natour; Jana Al Achcar; Rola Maadarani; Ghina Krayker; Bilal Azakir; Jad El Masri; Pascale Salameh (PLoS ONE, 2026)
Background Environmental exposure significantly influences mental well-being. Green spaces offer psychological benefits, while noise exposure is a recognized environmental stressor. However, their effects on mental health outcomes such as depression, anxiety, and stress remain underexplored in Lebanon. This study investigates the influence of green space and noise exposure on mental health in the Lebanese population. Methods A cross-sectional study was conducted using an online survey distributed across the Lebanese population. A total of 653 participants aged 18–65 years completed the questionnaire, which assessed socio-demographics, green space exposure, noise exposure, and mental health using the Arabic versions of the validated scales for depression (PHQ-9), anxiety (GAD-7), and stress (PSS-10). Data was analyzed using SPSS version 25. Results Higher green space exposure—such as proximity to greenery, views of natural environments, and more frequent visits—was significantly associated with lower levels of depression, anxiety, and stress (p < 0.05). Conversely, greater noise exposure at home or work, and symptoms such as sleep disturbance, irritability, or difficulty concentrating due to noise, were significantly associated with higher scores across all three mental health domains (p < 0.001). Multiple linear regression showed that some noise-related symptoms were consistently associated with higher depression, anxiety, and stress. Conclusions Environmental exposures play a critical role in shaping the mental health. Increasing access to green spaces and reducing noise pollution may serve as effective public health interventions to decrease levels of depression, anxiety, and stress among Lebanese residents. Urban planning and public policy should integrate these findings into mental health promotion strategies.